BANTUAN KEMANUSIAAN AUSTRALIA TERHADAP PENGUNGSI SURIAH - Isman Habibillah (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
This article analyzes Australian foreign policy relating to humanitarian aid to Syria.Foreign policy is the formulation of a policy that is the result of a combination ofdomestic conditions (domestic factors) and the constellation of international politics(global factors). Likewise with Australian foreign policy. In the formulation of theimplementation of foreign policy, certainly consider the domestic factors and theinternational political constellation that occurred at that time so that the policyformulated will be able to realize Australia's national interests. To show Australia'sconcerns about the disruption by the Syrian regime's violence against its people,Australia imposed new sanctions on Syria on 21 August 2012 restricting the trading ofprecious metals and diamonds, luxury goods, and newly minted currencies as well asto the oil, gas and petrochemical sectors . New measures add to the freezing ofexisting assets and travel restrictions on 106 individuals and 28 entities and anembargo on the supply of militaryequipment and assistance. Australian sanctionsspecifically target the regime, not the Syrian people. including sanctions againstsenior government figures, including President Assad, who is connected with violenceand human rights abuses. The research method used is qualitative research method,that is make description, picture or painting systematically, factual, accurate aboutfacts, properties and relationship between phenomena investigated.Keywords: Australian Foreign Policy, Syrian Crisis, Humanitarian Aid